CURRENT STATE AND EMERGING CHALLENGES IN THE AUDIT SECTOR OF MONGOLIA - Ganbaatar, Bayalag; Batbayar, Altan-Erdene (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study aims to evaluate the current state of the audit sector in Mongolia and identify the key factors affecting audit quality. The research framework is based on three core dimensions: input (auditor’s knowledge, experience, and ethics), process (quality control and independence), and output (usefulness and reliability of audit reports). Using a qualitative survey method, 70 professional auditors were surveyed. The findings highlight that factors such as audit team competence, quality control systems, and auditor independence have the strongest influence on audit quality. The study proposes recommendations to improve institutional support and strengthen national audit firms’ capacity.